Side-by-side comparison of flow cytometry and immunohistochemistry for detection of calreticulin exposure in the course of immunogenic cell death - Kasikova, Lenka; Truxova, Iva; Cremer, Isabelle; Sautes-Fridman, Catherine; Kepp, Oliver; Kroemer, Guido; Spisek, Radek; Fucikova, Jitka (Methods in enzymology, 2020)
Immunogenic cell death (ICD), a functionally peculiar type of apoptosis, represents a unique way to deliver danger-associated molecular patterns (DAMPs) to the tumor microenvironment. Once emitted by dying cancer cells, DAMPs orchestrate antigen-specific immune responses by acting on both innate and adaptive components of the immune system. Accumulating preclinical and clinical evidence indicates that one of these DAMPs, calreticulin (CALR) represents a novel powerful prognostic biomarker, reflecting the activation of a clinically relevant anticancer immune response in different cancer malignancies. Therefore, the assessment of CALR emission can provide a therapeutic tool for the stratification of cancer patients and the identification of individuals that are intrinsically capable to respond to a particular treatment. Here we describe methods for the quantification of CALR exposure in the tumor microenvironment of cancer patients by flow cytometry and immunohistochemistry.
Keywords: Flow cytometry; Animals; Immunogenic cell death; průtoková cytometrie; Neoplasms; nádory; nádorové mikroprostředí; Immunohistochemistry; Calreticulin; lidé; Flow Cytometry; imunohistochemie; nádorové biomarkery; kalretikulin; Biomarkers, Tumor; imunogenní buněčná smrt; Immunogenic Cell Death; Tumor Microenvironment; zvířata; Cancer prognosis; Humans